Path Analysis on the Determinants of the Use of Integrated Health Post and the Application of Theory of Planned Behavior - Yuni Fitriani; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Integrated health post (Posyandu) is a strategy for community empowerement. It has an important role to reduce maternal mortality rate (MMR) and infant mortality rate (IMR). The intergrated health post monitors the health of infants, children, pregnant women, lactating women, and women of reproductive age. Weighing coverage of children under five was only 80.4% in Central Java, in 2014. Weighing coverage of children under five was only 78.4 % in Tegal District, in 2015, which was lower than the expected target of 80%. This study aimed to investigate the determinant of of the use of integrated health post and the application of Theory of Planned Behavior (TPB).Subjects and method: This was an analytic observational study with case control design. This study was conducted in Tegal District, Central Java, from 25 September to 25 October 2016. A total sample of 135 mothers with their respective children aged 6-59 months were selected for this study by fixed disease sampling. The dependent variables were intention and use of the integrated health post. The independent variables were constructs of TPB, including attitude toward behavior, subjective norm, and perceived behavior control. The data were collected by a pre-tested set of questionnaire. The data were analyzed by path analysis using IBM SPSS AMOS 22.Results: The path model showed goodness of fit with CMIN=4.24; p=0.120; GFI=0.99; NFI=0.99; CFI=0.99; and RMSEA=0.09. Intention had direct positive and statistically significant effect on the use of the integrated health post (b=0.29; p<0.001). All of the three TPB constructs, including attitude toward behavior (b=0.27; p<0.001), subjective norm (b=0.27; p=0.046), and perceived behavior control (b=0.34; p=0.007) had indirect positive and statistically significant effect on the use of the integrated health post.Conclusion: Intention has direct positive effect on the use of the integrated health post. All of the three TPB constructs, i.e. attitude toward behavior, subjective norm, and perceived behavior control has positive and indirect effect on the use of the integrated health post.Keywords: integrated health post, theory of planned behaviorCorrespondence: Yuni Fitriani. School of Health and Sciences, STIKes Bhakti Mandala Husada Slawi. Email: yfitriani85@yahoo.co.id.Journal of Health Promotion and Behavior (2016), 1(4): 228-237https://doi.org/10.26911/thejhpb.2016.01.04.02